1997
DOI: 10.1023/a:1006557228604
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Studies were conducted on the hypothesis that melanoma metastasis might be initiated through the generation of hybrids comprised of cells of the primary tumor and tumor-infiltrating leukocytes. Fusion hybrids were generated in vitro between weakly metastatic Cloudman S91 mouse melanoma cells and normal mouse or human macrophages. Hybrids were implanted s.c. in the tail and mice were monitored for metastases. Controls included parental S91 cells, autologous S91 x S91 hybrids, and B16F10 melanoma cells. Of 35 hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 77 publications
4
74
0
Order By: Relevance
“…It has been suggested that cancer cells may spontaneously fuse with host cells to produce hybrids (17, 18, 35, 49, 50). Evidence in support of cancer cell fusion with macrophages or other bone marrow-derived cells has been reported from studies of animal models of human cancer (6, 9-11, 49, 52, 53, 59). Hybrid cells formed from macrophages and melanoma cells may possess the malignant potential of the melanoma cells and the migratory phenotype of the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cancer cells may spontaneously fuse with host cells to produce hybrids (17, 18, 35, 49, 50). Evidence in support of cancer cell fusion with macrophages or other bone marrow-derived cells has been reported from studies of animal models of human cancer (6, 9-11, 49, 52, 53, 59). Hybrid cells formed from macrophages and melanoma cells may possess the malignant potential of the melanoma cells and the migratory phenotype of the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that cell fusion contributes to cancer progression was introduced almost 100 years ago with a proposal that malignancy is a consequence of hybridization between leukocytes and somatic cells, and Melanoma × macrophage hybrids with enhanced metastatic potential [40]. Years later, this idea was expanded to encompass that cell fusion promotes the phenotypic and genotypic diversity of tumors and that the fusion of tumor cells with leukocytes results in metastatic cells [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…At least some of these hybrids become metastatic, exhibiting both motility and continuous cell division 70 . It has been demonstrated that hybrids of weakly metastatic Cloudman S91 mouse melanoma cells and normal mouse or human macrophages can be created in vitro with use of polyethylene glycol -induced fusion 71 . Compared to the parental melanoma cells, most daughters of the 35 hybrids tested were found to be more aggressive, with the result being that metastases onset was more rapid and observed in greater numbers of mice 71 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that hybrids of weakly metastatic Cloudman S91 mouse melanoma cells and normal mouse or human macrophages can be created in vitro with use of polyethylene glycol -induced fusion 71 . Compared to the parental melanoma cells, most daughters of the 35 hybrids tested were found to be more aggressive, with the result being that metastases onset was more rapid and observed in greater numbers of mice 71 . The majority of these hybrid clones showed markedly enhanced chemotactic motility toward a variety of attractants in 2-chambered culture systems, a hallmark of metastatic cells 72 .…”
Section: Introductionmentioning
confidence: 99%